Menerapkan Sistem Informasi Akuntansi dalam Meningkatkan Transparansi Pengelolaan Keuangan Pamsimas pada Bumdes Giri Artha - Mega Leni Kusuma Yanti; Lucy Sri Musmini (Jurnal Akuntansi Profesi, 2020)
This study aims to determine (1) the application of accounting information systems in increasing the transparency of PAMSIMAS financial management at BUMDes Giri Artha Desa Tembok, and (2) the constraints and solutions of applying accounting information systems in increasing the transparency of PAMSIMAS financial management at BUMDes Giri Artha Desa Tembok. This research uses descriptive qualitative research. The data sources used are primary and secondary data. Primary data in the form of interviews from research subjects. While secondary data were obtained from various literatures related to this research topic. The data analysis technique used is the collection, reduction, presentation, data analysis and conclusion drawing. The results of this study explain that the accounting information system implemented by BUMDes Giri Artha is a pambumdesaku application that is able to increase transparency. As for several obstacles in the application of this application system, namely (1) the elderly who become pamdesa consumers who have difficulty in understanding the application being applied, (2) there are people whose economies are less able so that they are unable to pay bills that must be met. However, all of these obstacles can be overcome and coordinated by the BUMDes with PAMSIMAS members for the sustainability of consumers who can later improve the performance of the Giri Artha BUMdes.